Hormesis – an example of astrocyte response after ethanol exposure: Hormeza – primer odgovora astrocitov po izpostavljenosti etanolu - Lipnik–Štangelj, Metoda; Šarc, Lucija (Acta Medico-Biotechnica, 2021)
Purpose: In the present work we describe hormesis and review documented hormetic responses in astroglial cells after exposure to different stressors. We present an example of the astrocyte response to acute and chronic ethanol exposure with hormetic characteristics.Methods: As an experimental model, newborn rat cortical astrocytes in culture were used. The cells were exposed to ethanol or the primary metabolite of ethanol (acetaldehyde) for 24 h or 7 days. After treatment, the protein content was determined, and the IL–6 levels in the culture medium were measured using an enzyme– linked immunoassay.Results: Treatment of astroglial cells with ethanol or acetaldehyde led to enhanced protein content and stimulated IL–6 production in the low concentration zone followed by diminished protein content and an inhibition of IL–6 production at higher concentrations. Chronic exposure of astrocytes was more toxic than acute exposure for both compounds, and acetaldehyde was more toxic compared to ethanol.Conclusion: Ethanol and acetaldehyde represent stressors for cultured astrocytes and evoke a typical hormetic response after acute and chronic exposure.
Keywords: hormesis; astrocytes; ethanol; acetaldehyde